Setting standards for some defensive tests against scoring in futsal - العلواني, م.د. علي فيصل ضايف (Sulaimani Journal for Humanities, 2026)
Futsal is a fast-paced team sport that relies on constant interaction between players. It combines technical skills, physical fitness, and tactical intelligence. Due to its fast-paced, attacking nature, the defensive aspect is crucial in limiting scoring opportunities and maintaining balance on the field. The research problem lies in the lack of clear and standardized criteria for some defensive tests against scoring in futsal, which limits the possibility of scientifically and systematically evaluating players' defensive performance. This research aims to identify the most important defensive skills that influence scoring in futsal, determine a set of suitable tests to measure aspects of defensive performance against scoring, and analyze the results of these tests to describe the typical defensive performance of a futsal player. It also aims to establish quantitative reference standards for some defensive tests against scoring that can be used to evaluate players. Players from the Babylon Sports Club futsal team were selected as the population and sample for the research. The researcher used the descriptive-analytical method, and a sample of 30 players aged between 16 and 20 years was selected. The research results showed clear differences in players' defensive levels, measurable using specific and reliable tests. A set of field-applicable tests was developed to accurately measure aspects of defense against scoring and to establish numerical reference standards (norms) that can be used to evaluate defensive performance. The weakness in some players' defensive performance is attributed to a lack of specialized training programs focused on scoring situations. The researcher recommends adopting the standardized tests developed in this research as a primary tool for evaluating the defensive aspect in futsal and integrating these tests into training programs to continuously improve defensive performance. The researcher also recommends using the identified standards in player selection and guidance processes, especially for younger age groups, and conducting similar studies on different categories (age, skill level, and gender) to ensure comprehensiveness.
Keywords: Defense tests; scoring skills; futsal